PIECES FRAMEWORK ON THE IMPLEMENTATION OF RAPID ENUMERATION AND EVALUATION INFORMATION SYSTEM OF 2020 POPULATION CENSUS - Yuanita, Rizka Ita (Jurnal Pilar Nusa Mandiri, 2021)
In September 2020, Statistics Indonesia (BPS RI) carried out a major activity, namely the 2020 Population Census At the SP2020 data processing stage, Mobile Capture is one of the options for photographing data collection results. During the use of mobile capture, BPS West Java Province encountered several obstacles. West Java Province BPS created an application called the Rapid Enumeration dan Evaluation 2020 Population Census Information System (Sicepat32 SLS) to monitor the attainment of enumeration to the smallest level (local environmental unit). To find out whether Sicepat32 SLS is working and functioning properly, it is necessary to evaluate the performance of the information system. The purpose of this study is to measure the level of user satisfaction with the application of Sicepat32 SLS and to assess whether Sicepat32 SLS can meet the needs of users. In this study, the PIECES Framework analysis model will be used and has produced an assessment score in the Performance domain of 4.07; Information and Data of 4.17; Economy 4.1; Control and Security with a score of 4.03; Efficiency with a score of 4.18 and Service getting a score of 4.18